The Construction of Religious Messages: Objectives of Da’wah Language Styles in Undergraduate Theses - Julananda Putri Sahasti; Alfina Rahmatul Ulya (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to identify the purposes of using da’wah language styles in undergraduate theses of students from the Da’wah Management Study Program and to examine their role in supporting da’wah messages, religious values, social values, and character development in academic writing. Methodology: This study used qualitative research methods with an interpretive approach. Data were collected through semi-structured interviews and documentation. The research instruments included interview guidelines, document analysis sheets, and coding matrices. The data sources consisted of 20 graduates and 114 undergraduate thesis manuscripts from the Da’wah Management Study Program at FDK UIN Walisongo Semarang in 2025. Main Findings: The findings show that da’wah language styles in undergraduate theses include persuasive, empathetic, religious, contextual, and ethical expressions. These styles function to strengthen arguments, convey da’wah messages, build author credibility, and represent values of integrity, responsibility, empathy, social awareness, and ethical communication in academic writing. Novelty/Originality of this study: This study expands da’wah language research from oral and digital communication into academic writing. It introduces undergraduate theses as a medium for internalizing religious and character values in higher education. The study demonstrates that scientific writing can integrate academic reasoning, da’wah communication, social values, and student character development through ethical and responsible language practices.